An extraordinary new genus and species of Pseudachorutinae (Collembola: Neanuridae) from Colombia - Palacios-Vargas, José G. (Zootaxa, 2019)
A new genus of springtail, Sernatropiella gen. nov., from Cundinamarca province, Colombia, was found at an altitude close to 3.000 m above sea level. It is the largest Neanuridae known in the Northern part of the South American Transition Zone. It is characterized by the presence of a strong hypertrichosis, five eyes per side, very small moruliform postantennal organ and a long buccal beak. Mouth parts very thin and slender. Body with paratergal areas different from other Pseudachorutinae of the region. Thorax and abdominal segments I and II with pre- and post-segmental tergites with setae, and most remarkable is the presence of pseudocelli on head, thorax and abdomen of the type species Sernatropiella pinzonae gen. et sp. nov. A new combination for Neotropiella malkini Arlé, 1981 as Sernatropiella malkini (Arlé, 1981) comb. nov. is given and is considered as a member of the new genus.